Rancang bangun rehal Al Qur’an untuk posisi duduk bersila - Sunding, Alang; Ridhani, Ulia (Institut Seni Indonesia Yogyakarta, 2024)
Rehal is a support or stand with a certain height and slope used to place the holy book of the Qur'an in order to provide comfort, clarity and convenience for people who use it when reading the Qur’an when sitting on their knees, cross-legged, sitting on a chair or when standing. The focus of this research will be to design a rehal for the use of a cross-legged sitting position on the floor. The concept of design refers to the development stage that has been carried out by several previous studies in the form of a new design concept, from environmentally friendly materials, height is more than the height of the belly button. The research method is carried out with the stages of literature study to set product boundaries, design, review designs, make product prototypes and test designed products. The results of the study were in the form of a rehal with a new design made of multiplex material coated with pvc sheet, height size 30 cm, has a slope of 45 ° position of the Qur'an when used. The results of the rehal test are able to support the Qur'an up to A4 size with a stable position and visibility when reading the top and bottom rows is only 4 cm apart, so rehal provide comfort when used, compared to Rehal in general, the difference in visibility between the top row and the bottom row reaches 20 cm. The slope of the Qur'an is generally a horizontal slope while the result of the design with a vertical slope so that it will feel better than before.